2023
DOI: 10.4094/chnr.2023.29.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the mental health status of children from multicultural families in South Korea: a cross-sectional descriptive analysis of data from the multicultural adolescents panel study

Abstract: Purpose: This study aimed to identify factors affecting the mental health status of children from multicultural families in South Korea.Methods: This study was based on Dahlgren and Whitehead's (1991) rainbow model as a conceptual framework and used data from the second phase of the multicultural adolescents panel study conducted by the National Youth Policy Institute. Multiple logistic regression analysis was performed using SPSS version 26.0, with <i>p</i><.05 considered to indicate statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In another study that used the same life satisfaction scale [28], the average life satisfaction score of all multicultural adolescents, including children of Vietnamese mothers, was 3.33. In another study of a panel of multicultural adolescents using the same scale [15], the average life satisfaction score was 3.35. These findings were consistent with those of a previous study that found that the life satisfaction of children of immigrant mothers differed according to the mother's country of origin [16].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In another study that used the same life satisfaction scale [28], the average life satisfaction score of all multicultural adolescents, including children of Vietnamese mothers, was 3.33. In another study of a panel of multicultural adolescents using the same scale [15], the average life satisfaction score was 3.35. These findings were consistent with those of a previous study that found that the life satisfaction of children of immigrant mothers differed according to the mother's country of origin [16].…”
Section: Discussionmentioning
confidence: 96%
“…However, life satisfaction among Koreans is not high [14], and it is believed that this is especially true for children and adolescents from multicultural families who are relatively vulnerable and are culturally different. According to previous studies, multicultural school-aged children in Korea had higher stress scores and lower self-esteem scores than those of children of Korean parents [15]. In addition, the school adjustment and life satisfaction of children of immigrant mothers in Korea differed according to the mother's country of origin [16].…”
Section: Introductionmentioning
confidence: 95%